The worldview of Akkermansia muciniphila, a bibliometric analysis - Zhang, Zhao; Wang, Jingyu; Dang, Shaoqing; Liu, Xingzi; Zhang, Yuemiao; Zhang, Hong (Frontiers in Microbiology, 2025)
Akkermansia muciniphila (A. muciniphila), a critical bacterium within the gut microbiota, plays a key role in human health and immunomodulation. Since its identification in 2004, A. muciniphila has emerged as a significant agent in treating metabolic diseases, gastroenterological diseases, and tumor immunotherapy. Its rapid ascent in scientific translation underscores its importance in gut microbiome research. However, there has been a lack of visualization and analysis of the rapidly occurring commercialization in this field, which has critically hindered insights into the current knowledge structure and understanding of the cutting-edge of the discipline. This study employs the Web of Science Core Collection (WOSCC) and Innography platforms to provide the first comprehensive analysis of A. muciniphila’s academic progresses and commercialization over the past two decades, highlighting its growing prominence in global health research. Our analysis delineates that, following the academic trajectory, the evolution of A. muciniphila patents from foundational research through to application development and maturity, with particular emphasis on its expansive potential in emerging fields, including gastroenterological disorders, non-alcoholic fatty liver disease, cancer immunotherapy, stress management, and neurodegenerative disease treatment. Concluding, A. muciniphila presents as a next-generation probiotic with vast implications for human health. Our findings provide essential insights for future research and product development, contributing to the advancement of this burgeoning field.